Risk of violence and quality of life among the elderly in the community: cross-sectional study - Matheus Farias Raposo; Jefferson da Silva Soares; Gleicy Karine Nascimento de Araújo-Monteiro; Renata Clemente dos Santos; João Euclides Fernandes Braga; Rafaella Queiroga Souto; Barbara Maria Lopes da Silva Brandão (Universidade Federal do Ceará, 2021)
Objective: to analyze the relationship between the risk of violence and the quality of life of elderly community members. Methods: a cross-sectional study, developed with 159 elderly people registered in family health teams. The following instruments were used: Hwalek-Sengstock Elder Abuse Screening Test; World Health Organization Instrument to Evaluate Quality of Life. Results: the risk of violence was higher among the elderly with low quality of life through association tests (62.5%; p=0.380) and correlation (r=-0.244). There was a statistically significant difference (p=0.013) between quality of life of groups with and without risk for violence, and the analysis of logistic regression confirms that high quality of life is a protective factor for the exposure of the elderly to situations of abuse (Odds Ratio = 0.96; p=0.01). Conclusion: there was an inverse relationship between quality of life and risk of violence.